"NATIONAL IDENTITY VS. EUROPEAN IDENTITY: PARTNERS OR RIVALS" - Apostolovska Stepanoska, Milena; Runcheva-Tasev, Hristina (УКИМ, Правен факултет „Јустинијан Први“, 2017)
This paper aims to analyze whether the European identity can be equated with the national identity. The authors make an attempt to define the European identity through the markers of national identity given by the famous theorist and researcher of national identity Anthony Smith. The paper presents an overview of the theory of the national identity from Anthony Smith and the standpoints of the most relevant authors and theorists in the field of European identity. The authors of the paper come to a conclusion that: the European identity can’t be theorized with the national identity definitions and that the existence of